Extraction and evaluation of sago hampas and bark - Siti Asma', bt Kram. (Universiti Malaysia Sarawak (UNIMAS), 2004)
Sago palm ( Metroxylon sp. ) which belongs to the family of palmae contains a high percentage of starch and other chemical composition such as lignin, extractives and polysaccharide. The study was done to determine the chemical composition by using T APPI standard reference. The hampas and the sago bark were obtained from the sago indu trial mill in Sibu, Sarawak. The determination of extraneous components such as tannins, gums, sugars, coloring matter was determine by using cold water solubility and hot water solubility experiment. The Ethanol acetone determination was used to determine the percentage of waxes, fats, resins and other other insoluble components in the sago hampas and sago bark. The hot alkali of 1% NAOH determined the acidity of the sample. To evaluate the sago hampas and sago bark hardness, bleachability and other pulp properties such as color the determination of lignin was used (72 % of sulfuric acid reagent was used to extract the lignin content). For the holocellulose determination, the sodium chlorite powder have been utilized as the main chemical reagent to oxidize the sample. Mean while, for the determination of the percentage of a-cellulose, the strong 17.5 % NAOH was used. The slide was prepared to measured the fiber length, fiber width and fiber thickness. The starch content have been determined by the absorbance value of starch at 580 run in spectrophotometer against a reference solution of 25 ml HCL and 2.5 ml KI-I. From this study, sago hampas recorded higher percentage in cold water solubility, hot water solubility, I % NAOH solubility, holocellulose ,ash content and starch content than sago bark which comprised the higher percentage in ethanol acetone solubility, lignin and a-cellulose determination. In the measurement of fibre, the fibre length in sago hampas was much higher than sago bark, the width of fibre bark was wider and the fibre thickness in sago bark also recorded higher value than sago bark. The ago density in sago bark was higher than sago hampas.